COVID-19: Targeting Proteases in Viral Invasion and Host Immune Response - Seth, Sanchit; Batra, Jyotsna; Srinivasan, Srilakshmi (Frontiers in Molecular Biosciences, 2020)
An acute respiratory disorder (COVID-19) that accelerated across the globe has been found to be caused by a novel strain of coronaviruses (SARS-CoV-2). The absence of a specific antiviral drug or vaccination has promoted the development of immediate therapeutic responses against SARS-CoV-2. As increased levels of plasma chemokines and, cytokines and an uncontrolled influx of inflammatory cells were observed in lethal cases, it was concluded that the severity of the infection corresponded with the imbalanced host immunity against the virus. Tracing back the knowledge acquired from SERS and MERS infections, clinical evidence suggested similar host immune reactions and host ACE2 receptor-derived invasion by SARS-CoV-2. Further studies revealed the integral role of proteases (TMPRSS2, cathepsins, plasmin, etc.) in viral entry and the immune system. This review aims to provide a brief review on the latest research progress in identifying the potential role of proteases in SARS-CoV-2 viral spread and infection and combines it with already known information on the role of different proteases in providing an immune response. It further proposes a multidisciplinary clinical approach to target proteases specifically, through a combinatorial administration of protease inhibitors. This predictive review may help in providing a perspective to gain deeper insights of the proteolytic web involved in SARS-CoV-2 viral invasion and host immune response.